Defects of clean graphene and sputtered graphite surfaces characterized by time-of-flight secondary ion mass spectrometry and X-ray photoelectron spectroscopy. (February 2017) - Xie, Wenjing; Weng, Lu-Tao; Ng, Kai Mo; Chan, Chak K.; Chan, Chi-Ming
Abstract: Clean surface of graphene was obtained at 500 °C and characterized by X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS). In the XPS C1s spectrum of graphene, besides an asymmetric sp 2 carbon peak and a π-π ∗ shake-up peak appeared, an additional sp 3 carbon peak representing sp 3 defects was also present. In the ToF-SIMS positive ion spectrum of graphene, a series of Cx H2 + ions originated from the defects of graphene was found. To determine the origin of the Cx H2 + ions, defects were created on the surface of nearly defect-free highly oriented pyrolytic graphite (HOPG) by bombarding it with a Cs + ion beam at various sputtering doses. A detailed examination of the positive ion spectra of ion-bombarded HOPG surfaces reveals the presence of the Cx H2 + ions, confirming that these Cx H2 + ions, which came from the defects created on the sputtered HOPG surfaces, are similar to the defects present on graphene surface. A sp 3 carbon peak at 285.3 eV, representing sp 3 defects appeared in the XPS spectra of sputtered HOPG samples, confirms that the surface of the sputtered HOPG is similar to that of graphene. Fragmentation mechanisms of selected ions in the ToF-SIMS spectra of graphene and HOPG were proposed. Graphical abstract: